Aluminum alloy fin material and its manufacturing method
The aluminum alloy fin material, with its tailored chemical composition and crystal texture, addresses the challenge of balancing strength and moldability, enabling the creation of lighter and more efficient heat exchangers.
Patent Information
- Application Number
- JP2021015823
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-02-03
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2041-02-03
AI Technical Summary
Existing aluminum alloy fin materials struggle to balance strength and moldability, particularly when reduced in thickness to meet demands for lighter and smaller heat exchangers.
An aluminum alloy fin material is developed with a core material containing specific chemical compositions of Si, Fe, and Mn, and a brazing material made of an Al-Si alloy. The core material has a controlled crystal texture, and the manufacturing process includes casting, lamination, hot rolling, cold rolling, and annealing to achieve the desired properties.
The resulting fin material exhibits excellent strength and moldability, allowing for the production of heat exchangers with improved performance and reduced thickness.
Smart Images

Figure 0007653266000008 
Figure 0007653266000001 
Figure 0007653266000002
Abstract
Description
[Technical field]
[0001] The present invention relates to an aluminum alloy fin material and a manufacturing method thereof. [Background technology]
[0002] Heat exchangers such as condensers, radiators, heater cores, and intercoolers are often made of aluminum alloys, which have both high specific strength and high thermal conductivity among metals. This type of heat exchanger may have corrugated fins. Heat exchangers with corrugated fins are manufactured, for example, by forming a fin material into a desired shape, combining it with other members, and brazing it. The fin material is a brazing sheet in which a core material and a brazing material are laminated on both sides of the core material.
[0003] In recent years, there has been a strong demand for lighter and smaller heat exchangers in various technical fields, such as the automotive field. To meet such demands, there is also a demand for thinner fin materials used in heat exchangers while maintaining their strength.
[0004] In response to such demands, for example, Patent Document 1 describes an aluminum alloy brazing sheet fin material in which the core material contains 0.05-0.8 mass% Si, 0.05-0.8 mass% Fe, and 0.8-2.0 mass% Mn, and the contents of Si, Fe, and Mn satisfy the condition of Si+Fe≦Mn, with the balance being Al and unavoidable impurities, and the brazing material contains 6.0-13.0 mass% Si, 0.05-0.8 mass% Fe, with the balance being Al and unavoidable impurities. The fin material in Patent Document 1 aims to improve the strength after brazing heat by controlling the metal structure of the core material before and after brazing heat to a specific state. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. 2016 / 147627 Summary of the Invention [Problem to be solved by the invention]
[0006] Corrugated fins incorporated in heat exchangers are sometimes given complex shapes such as slits and louvers to improve heat exchange efficiency. When trying to make heat exchangers more compact, the dimensions of the slits and louvers become smaller than before, so the fin material is required to have better formability than before.
[0007] However, there is a trade-off between strength and formability, and when trying to improve formability, strength tends to decrease. The fin material of Patent Document 1 still has room for improvement from the viewpoint of achieving both high strength and excellent formability.
[0008] The present invention has been made in consideration of the above background, and aims to provide an aluminum alloy fin material having excellent strength and formability, and a method for manufacturing the same. [Means for solving the problem]
[0009] One aspect of the present invention is an aluminum alloy fin material comprising a brazing sheet having a core material and a brazing material arranged on both sides of the core material, The core material is A chemical composition containing Si (silicon): 0.02% by mass or more and 0.80% by mass or less, Fe (iron): 0.02% by mass or more and 0.80% by mass or less, and Mn (manganese): 0.8% by mass or more and 2.0% by mass or less, with the remainder being Al (aluminum) and unavoidable impurities; a crystal texture in which the orientation density of one or more of the crystal orientations of Brass orientation, Copper orientation, and S orientation is 20 times or more that of a random orientation sample, and the orientation density of the Cube orientation, CR orientation, and P orientation is all 10 times or less that of a random orientation sample; The brazing material is made of an Al-Si alloy containing Si: 6.0 mass% or more and 13.0 mass% or less and Fe: 0.02 mass% or more and 0.80 mass% or less, The aluminum alloy fin material has a cladding ratio of 6% or more and 16% or less for each of the brazing filler metals.
[0010] Another aspect of the present invention is a method for producing the aluminum alloy fin material of the above aspect, a casting process for producing an ingot for a core material having a chemical composition containing Si: 0.02% by mass to 0.80% by mass, Fe: 0.02% by mass to 0.80% by mass, Mn: 0.8% by mass to 2.0% by mass, with the balance being Al and unavoidable impurities, and an ingot for a brazing material made of an Al-Si alloy containing Si: 6.0% by mass to 13.0% by mass, and Fe: 0.02% by mass to 0.80% by mass; a lamination step of disposing the brazing material block on both sides of the core material block to prepare a clad block; a hot rolling step of hot rolling the clad ingot to produce a clad plate; A first cold rolling step of cold rolling the clad plate; The clad plate after the first cold rolling step is subjected to a total diffusion amount M calculated by the following formula (1) of 1.0 × 10 -14 m 2 Above 5.0×10 -12 m 2 An annealing process of heating and annealing under the following conditions; and a second cold rolling step of cold rolling the clad plate after the annealing step.
[0011]
number
[0012] In the above formula (1), n is the number of intervals when the total heating time is divided by the unit time Δt, and D0 is 1.37 × 10 -5 m 2 / s, Q is 123 kJ / mol, the value of R is 8.3145 kJ / (mol K), and the value of T(k) is the heating temperature [K] at the start of the kth interval. Effect of the Invention
[0013] The aluminum alloy fin material (hereinafter referred to as "fin material") is composed of a brazing sheet having a core material and a brazing material arranged on both sides of the core material. The core material has the specific chemical components and a crystal texture specified by the orientation density of each of the crystal orientations. The fin material has excellent formability by making the chemical components and crystal texture of the core material before brazing heat into the specific form.
[0014] Furthermore, when the core material is subjected to brazing heat, fine precipitates can be formed in the core material, which can improve the strength of the core material, i.e., the strength of the fin.
[0015] Therefore, the fin material has excellent formability before the brazing heat and has high strength after brazing.
[0016] The fin material can be produced by the manufacturing method of the above-mentioned embodiment. In the manufacturing method, an annealing step is performed between the first cold rolling step and the second cold rolling step, in which the clad plate is heated and annealed under conditions in which the total diffusion amount M is in the specific range. By setting the total diffusion amount M in the annealing step to the specific range, the crystal texture of the core material of the finally obtained fin material can be easily set to the specific embodiment. Therefore, the fin material can be easily obtained by the manufacturing method of the above-mentioned embodiment.
[0017] As described above, according to the above-mentioned aspect, an aluminum alloy fin material having excellent strength and formability and a manufacturing method thereof can be provided. [Brief description of the drawings]
[0018] [Figure 1]FIG. 1 is a cross-sectional view of an aluminum alloy fin material in an embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] (Fin material) The fin material is composed of a so-called double-sided brazing sheet including a core material and a brazing material arranged on both sides of the core material. More specifically, the brazing sheet constituting the fin material may be composed of three layers, namely, the core material and the brazing material laminated on both sides of the core material. The brazing sheet constituting the fin material may have four or more layers including, for example, the core material, the brazing material, and a layer made of an aluminum alloy other than the core material and the brazing material. Examples of layers that may be included in the brazing sheet include a skin material exposed on the outermost surface of the brazing sheet and an intermediate material interposed between the core material and the brazing material.
[0020] <Heartwood> The core material has a chemical composition containing Si: 0.02% to 0.80% by mass, Fe: 0.02% to 0.80% by mass, Mn: 0.8% to 2.0% by mass, with the balance being Al and unavoidable impurities, and a crystal texture in which the orientation density of at least one of the crystal orientations of Brass orientation, Copper orientation, and S orientation is 20 times or more that of a random orientation sample, and the orientation density of the crystal orientations of Cube orientation, CR orientation, and P orientation is 10 times or less that of a random orientation sample. The chemical composition and crystal texture of the core material and the reasons for these limitations will be explained below.
[0021] [Chemical composition] Si (silicon): 0.02% by mass or more and 0.80% by mass or less The core material contains 0.02% to 0.80% by mass of Si as an essential component. Together with Mn and Fe, Si forms Al-Mn-Si compounds and Al-Mn-Si-Fe compounds in the core material after brazing heating, and has the effect of improving the strength of the core material through precipitation strengthening.
[0022] By making the Si content in the core material 0.02 mass% or more, the number of Al-Mn-Si compounds formed in the core material can be sufficiently increased, and the strength of the core material after brazing heat can be improved. From the viewpoint of further increasing the strength of the core material after brazing heat, the Si content in the core material is preferably 0.04 mass% or more. If the Si content in the core material is less than 0.02 mass%, the amount of Al-Mn-Si compounds formed in the core material after brazing heat becomes insufficient, which may lead to a decrease in the strength of the core material after brazing heat.
[0023] On the other hand, if the content of Si in the core material is high, the amount of Si dissolved in the core material increases, which tends to lower the melting point of the core material. If the melting point of the core material is excessively lowered, the core material may be eroded by the brazing material during brazing heating, which may make the core material more likely to melt. By setting the content of Si in the core material to 0.80 mass% or less, preferably 0.70 mass% or less, and more preferably 0.60 mass% or less, such problems can be easily avoided.
[0024] Fe (iron): 0.02% by mass or more and 0.80% by mass or less The core material contains 0.02% by mass to 0.80% by mass of Fe as an essential component. Fe promotes the formation of Al-Mn-Si compounds and Al-Mn-Si-Fe compounds in the core material to improve the strength after brazing, and also has the effect of stabilizing the crystal structure of the core material.
[0025] By making the Fe content in the core material 0.02 mass% or more, it is possible to improve the strength of the core material after brazing and stabilize the crystal structure. From the viewpoint of further enhancing these effects, it is preferable that the Fe content in the core material is 0.05 mass% or more. If the Fe content in the core material is less than 0.02 mass%, the amount of Al-Mn-Si compounds and Al-Mn-Si-Fe compounds formed in the core material will be insufficient, which may lead to a decrease in the strength of the core material after brazing.
[0026] On the other hand, if the content of Fe in the core material is high, coarse crystallized particles are likely to be formed in the core material ingot when the core material ingot is cast in the manufacturing process of the fin material. The coarse crystallized particles in the core material ingot may cause difficulty in manufacturing the fin material or may lead to a decrease in the formability of the fin material. By setting the content of Fe in the core material to 0.80 mass% or less, preferably 0.70 mass% or less, the formation of coarse crystallized particles can be easily avoided.
[0027] Mn (manganese): 0.8% by mass or more and 2.0% by mass or less The core material contains 0.8% by mass or more and 2.0% by mass or less of Mn as an essential component. Some of the Mn dissolves in the core material after brazing heat and has the effect of improving the strength of the core material by solid solution strengthening. The remaining Mn forms Al-Mn-Si compounds and Al-Mn-Si-Fe compounds in the core material together with Si and Fe and has the effect of improving the strength of the core material after brazing by precipitation strengthening.
[0028] By making the Mn content in the core material 0.8 mass% or more, the effects of solid solution strengthening and precipitation strengthening can be enhanced, and the strength of the core material after brazing heat can be improved. From the viewpoint of further increasing the strength of the core material after brazing heat, the Mn content in the core material is preferably 1.0 mass% or more. If the Mn content in the core material is less than 0.8 mass%, the amount of solid solution of Mn in the core material after brazing heat and the amount of Al-Mn-Si compounds formed in the core material will be insufficient, which may lead to a decrease in the strength of the core material after brazing heat.
[0029] On the other hand, if the Mn content in the core material is high, coarse crystallized particles are likely to form in the core material ingot when the core material ingot is cast in the manufacturing process of the fin material. The coarse crystallized particles in the core material ingot may cause difficulty in manufacturing the fin material or may lead to a decrease in the formability of the fin material. By setting the Mn content in the core material to 2.0 mass% or less, preferably 1.8 mass% or less, the formation of coarse crystallized particles can be easily avoided.
[0030] Zn (zinc): 0.3% by mass or more and 3.0% by mass or less In addition to the essential components of Si, Fe, and Mn, the core material may contain Zn: 0.3% by mass or more and 3.0% by mass or less as an optional component. By adding Zn in the specific range to the core material, the potential of the core material can be appropriately lowered, and the core material after brazing, that is, the fin in the heat exchanger, can function as a sacrificial anode. As a result, the sacrificial corrosion protection effect of the fin can suppress corrosion of components other than the fin in the heat exchanger, such as tubes, for a longer period of time. From the viewpoint of improving the self-corrosion resistance of the fin while ensuring the sacrificial corrosion protection effect of the fin, the content of Zn in the core material is preferably 0.5% by mass or more and 2.8% by mass or less, more preferably 0.7% by mass or more and 2.7% by mass or less.
[0031] Other elements The core material may contain trace amounts of elements other than the above-mentioned elements as long as the above-mentioned effects are not impaired. Examples of elements that may be contained in the core material include Mg (magnesium), Cr (chromium), Ti (titanium), Zr (zirconium), and Cu (copper). The content of these elements should be 0.05% by mass or less for each element, and the total content should be 0.15% by mass or less.
[0032] [Crystal texture] Before brazing heating, the core material has a crystal texture in which the orientation density of at least one of the crystal orientations, Brass orientation, Copper orientation, and S orientation, is 20 times or more that of a random orientation sample, and the orientation density of the Cube orientation, CR orientation, and P orientation is 10 times or less that of a random orientation sample.
[0033] The above-mentioned crystal orientations are typical crystal orientations present in aluminum alloys. The degree of development of a crystal orientation can be expressed by the magnitude of the orientation density, and the higher the orientation density of a certain crystal orientation, the more developed that crystal orientation is. The orientation density of a crystal orientation can be calculated based on the diffraction intensity of that crystal orientation in an X-ray diffraction chart. The magnitude of the orientation density is expressed as the ratio of the orientation density of the corresponding crystal orientation in the sample to the orientation density of the corresponding crystal orientation in the sample to be measured, when the orientation density of the crystal orientation in a random orientation sample, i.e., a sample in which the distribution of crystal orientations is disordered, is used as the standard.
[0034] Among the above-mentioned crystal orientations, the Brass orientation, the Copper orientation, and the S orientation have the effect of increasing the work hardening index of the aluminum alloy. Therefore, by making the orientation density of one or more of the Brass orientation, the Copper orientation, and the S orientation in the core material before the brazing heat 20 times or more the orientation density of the corresponding crystal orientation in the random orientation sample, the work hardening index of the core material before the brazing heat can be increased. If the orientation densities of the Brass orientation, the Copper orientation, and the S orientation in the core material before the brazing heat are all less than 20 times that of the random orientation sample, the effect of improving the work hardening index by these crystal orientations may be reduced.
[0035] In addition, the Cube orientation, CR orientation, and P orientation have the effect of lowering the work hardening index of the aluminum alloy. Therefore, by making the orientation densities of the Cube orientation, CR orientation, and P orientation in the core material before brazing heat 10 times or less than the orientation density of the corresponding crystal orientation in the random orientation sample, it is possible to avoid a decrease in the work hardening index of the core material before brazing heat. If the orientation density of one or more of the Cube orientation, CR orientation, and P orientation in the core material before brazing heat is more than 10 times that of the random orientation sample, these crystal orientations may cause a decrease in the work hardening index.
[0036] Therefore, by making the crystal texture of the core material before brazing the core material into the specific form, the work hardening index of the core material can be increased. Such a core material can be easily deformed by forming such as pressing. Furthermore, since the strength of such a core material increases due to work hardening after deformation, the shape imparted by forming can be easily maintained. As a result, the fin material including the core material has excellent formability.
[0037] <Brazing material> The fin material has a brazing material on both sides of the core material. The brazing material arranged on one side of the core material and the brazing material arranged on the other side may have the same chemical composition, or may have different chemical compositions. The brazing material is composed of an Al-Si alloy containing Si: 6.0 mass% to 13.0 mass% and Fe: 0.02 mass% to 0.80 mass%. More specifically, the Al-Si alloy constituting the brazing material may have a chemical composition containing, for example, Si: 6.0 mass% to 13.0 mass% and Fe: 0.02 mass% to 0.80 mass%, with the balance being Al and unavoidable impurities.
[0038] ·Si: 6.0 mass% or more and 13.0 mass% or less The brazing filler metal contains 6.0% by mass or more and 13.0% by mass or less of Si as an essential component. The Si in the brazing filler metal lowers the melting point of the brazing filler metal and increases the fluidity of the brazing filler metal. In addition, some of the Si in the brazing filler metal diffuses into the core material during brazing heating and dissolves in the core material, or forms Al-Mn-Si compounds together with the dissolved Mn in the core material. In addition, it has the effect of improving the strength of the core material after brazing through solid solution strengthening and precipitation strengthening.
[0039] By making the Si content in the brazing material 6.0 mass% or more, preferably 6.5 mass% or more, it is possible to improve the brazing property with the mating material and to improve the strength of the core material after brazing. If the Si content in the brazing material is less than 6.0 mass%, the diffusion of Si from the brazing material to the core material during brazing heating becomes insufficient, which may lead to a decrease in the strength of the core material after brazing.
[0040] On the other hand, if the content of Si in the brazing material is high, the amount of Si diffusing from the brazing material to the core material during brazing heat increases. If the amount of Si diffusing into the core material is excessively high, the Mn dissolved in the core material is excessively consumed due to the formation of Al-Mn-Si compounds and the like. As a result, the amount of Mn dissolved in the core material after brazing is insufficient, which may lead to a decrease in strength. Furthermore, in this case, the amount of brazing material generated during brazing heat becomes excessively large, which may lead to a decrease in self-corrosion resistance. These problems can be easily avoided by setting the content of Si in the brazing material to 13.0 mass% or less, preferably 12.0 mass% or less.
[0041] ·Fe: 0.02 mass% or more and 0.80 mass% or less The brazing filler metal contains 0.02 mass % to 0.80 mass % of Fe as an essential component. The Fe in the brazing filler metal has the effects of increasing the fluidity of the brazing filler metal and improving its own corrosion resistance.
[0042] By making the Fe content in the brazing material 0.02 mass% or more, preferably 0.05 mass% or more, and more preferably 0.10 mass% or more, the fluidity of the brazing material can be increased and the self-corrosion resistance can be improved. If the Fe content in the brazing material is less than 0.02 mass%, the fluidity of the brazing material may decrease.
[0043] On the other hand, if the content of Fe in the brazing filler metal is high, coarse crystallized particles are likely to be formed in the brazing filler metal block during the manufacturing process of the fin material when the brazing filler metal block is cast. The coarse crystallized particles in the brazing filler metal block may cause difficulty in manufacturing the fin material or may lead to a decrease in the formability of the fin material. These problems can be easily avoided by setting the content of Fe in the brazing filler metal to 0.80 mass% or less, preferably 0.70 mass% or less, and more preferably 0.60 mass% or less.
[0044] Sr (strontium): 0.005% by mass or more and 0.050% by mass or less The brazing filler metal may contain, in addition to the essential components of Si and Fe, an optional component of Sr: 0.005% by mass or more and 0.050% by mass or less. Sr in the brazing filler metal has the effect of improving the fluidity of the brazing filler metal. By adding Sr in the specific range to the brazing filler metal, the brazing property can be further improved.
[0045] Other elements The brazing material may contain trace amounts of elements other than the above-mentioned elements as long as the above-mentioned effects are not impaired. Examples of elements that may be contained in the brazing material include Mg, Cr, Ti, Zr, and Cu. The content of each of these elements may be 0.05% by mass or less, and the total content may be 0.15% by mass or less.
[0046] <Thickness> The thickness of the fin material can be appropriately set within the range of, for example, 40 μm or more and 140 μm or less.
[0047] <Clad ratio> The cladding ratio of each brazing material in the fin material is 6% or more and 16% or less. By making the cladding ratio of each brazing material 6% or more, the amount of brazing material generated during brazing heating can be sufficiently increased, and the amount of Si diffused from the brazing material to the core material can be appropriately increased. As a result, the brazing property can be improved and the strength of the core material after brazing can be improved. If the cladding ratio of any brazing material is less than 6%, there is a risk of deterioration of brazing property due to insufficient brazing material and reduction in the strength of the core material after brazing.
[0048] On the other hand, when the cladding ratio is high, the amount of Si that diffuses from the brazing material to the core material during brazing heat increases, and the Mn dissolved in the core material is easily consumed. As a result, the effect of improving strength by solid solution strengthening decreases, and there is a risk of the strength of the core material after brazing decreasing. By setting the cladding ratio of the brazing material to 16% or less, preferably 14% or less, and more preferably 12% or less, such problems can be easily avoided.
[0049] <Work hardening index> The fin material preferably has a characteristic that the work hardening index at the yield point is 0.07 or more, and more preferably 0.08 or more. The work hardening index is an index that indicates the degree of increase in strength due to work hardening when the same strain is applied, and a larger value of the work hardening index means a larger increase in strength.
[0050] A fin material having a work hardening index in the specific range can increase the strength by a forming process such as press working. Therefore, when forming, the fin material can be easily deformed into a desired shape, and after the forming process is completed, the shape imparted by the forming process can be easily maintained. In this way, by setting the work hardening index of the fin material in the specific range, the formability of the fin material can be further improved.
[0051] The work hardening index of the fin material can be calculated by the following method. First, a No. 13B test piece specified in JIS Z2241:2011 is taken from the fin material so that the longitudinal direction is parallel to the rolling direction. Next, a tensile test is performed in a room temperature environment according to the method specified in JIS Z 2241:2011. Then, from the test force-strain curve obtained by the tensile test, the test force and plastic strain values at the yield point and the test force value at the point where the plastic strain has increased by 0.1% from the yield point are specified. Then, the work hardening index calculated by the two-point method using these values is set as the work hardening index of the fin material.
[0052] More specifically, the work hardening exponent n of the fin material is a value calculated by the following formula (2) using the test force F1 (unit: N) and plastic strain e1 (unit: %) at the yield point, and the test force F2 (unit: N) at the point where the plastic strain has increased by 0.1% from the yield point.
[0053]
number
[0054] (Method of manufacturing fin material) The fin material is produced by a manufacturing method including, for example, a casting process for producing a plurality of aluminum alloy ingots including a core ingot which will become the core material and a brazing material ingot which will become the brazing material; a stacking process for arranging the brazing material ingots on both sides of the core ingot to produce a clad ingot; a hot rolling process for hot rolling the clad ingot to produce a clad plate; a first cold rolling process for cold rolling the clad plate; an annealing process for heating and annealing the clad plate after the first cold rolling process; and a second cold rolling process for cold rolling the clad plate after the annealing process.
[0055] <Casting process> In the casting process, the method for producing the core material ingot and the brazing material ingot is not particularly limited. As the method for producing the core material ingot and the brazing material ingot, for example, a known casting method such as semi-continuous casting can be adopted. When producing the core material ingot by semi-continuous casting, casting may be performed so that the average cooling rate from when the molten metal is supplied to the die until it solidifies is 0.5° C. / sec or more.
[0056] Furthermore, when producing the core ingot by semi-continuous casting, it is preferable to cool the core ingot so that the average cooling rate from the point when the temperature of the core ingot reaches 550°C to the point when it reaches 200°C is 0.10°C / sec or more. By setting the average cooling rate of the core ingot within the above-mentioned specific range, it is possible to avoid excessive precipitation of Al-Mn-Si compounds and the like in the core ingot. From the same viewpoint, it is more preferable to cool the core ingot so that the average cooling rate from the point when the temperature of the core ingot reaches 550°C to the point when it reaches 200°C is 0.13°C / sec or more.
[0057] The core material ingot and brazing material ingot obtained in the casting process may be directly subjected to the lamination process. Alternatively, the core material ingot and / or brazing material ingot may be subjected to surface grinding to remove the ingot segregation layer formed on the surface, and then the core material ingot may be subjected to the lamination process. Furthermore, the core material ingot and / or brazing material ingot may be subjected to hot rolling to adjust the thickness thereof so that the cladding ratio of the finally obtained fin material is a desired value. When it is intended to produce a fin material having a layer made of an aluminum alloy other than the core material and brazing material, in addition to the core material ingot and brazing material ingot, an aluminum alloy ingot other than the core material and brazing material ingot may be produced in the casting process.
[0058] <Homogenization process> The manufacturing method may include a homogenization step of heating and homogenizing the core ingot after the casting step and before the lamination step. In the homogenization step, the holding temperature can be appropriately selected from the range of 420° C. or higher and lower than 510° C., and the holding time can be appropriately selected from the range of 0.5 hours or higher and 12 hours or lower, for example.
[0059] <Lamination process> In the lamination process, the brazing filler material ingot and the aluminum alloy ingot other than the brazing filler material ingot, which is provided as needed, are laminated on both sides of the core material ingot to produce a clad ingot. By producing the clad ingot in this manner, a fin material having brazing filler material disposed on both sides of the core material can be obtained.
[0060] <Hot rolling process> In the hot rolling process, the clad ingot is hot rolled to bond adjacent ingots in the clad ingot to each other while reducing their thickness. This makes it possible to obtain a clad plate in which the brazing material is arranged on both sides of the core material. In the hot rolling process, the clad ingot is preheated to a temperature range of 420°C to 500°C, preferably 430°C to 490°C, and then hot rolled. By setting the rolling start temperature to the specific range, adjacent ingots can be easily bonded to each other while avoiding excessive precipitation of Al-Mn-Si compounds in the core material in the clad plate. This makes it possible to sufficiently increase the amount of Mn dissolved in the core material in the finally obtained fin material, improve the formability of the fin material before brazing, and improve the strength of the fin after brazing.
[0061] When preheating the core ingot, it is preferable to perform preheating so that the holding time at the rolling start temperature is 0.5 to 12 hours. By setting the holding time within the above-mentioned specific range, excessive precipitation of Al-Mn-Si compounds and the like in the core can be more reliably avoided. From the same viewpoint, it is preferable to preheat the core ingot so that the time from the start of preheating to the time when the rolling start temperature is reached is 15 hours or less.
[0062] In the hot rolling process, it is preferable to perform hot rolling so that the temperature of the clad plate at the time when the reduction rate in hot rolling, that is, the reduction rate of the thickness of the clad plate relative to the thickness of the clad ingot at the start of hot rolling, reaches 10% is 370°C or more and 450°C or less, and it is more preferable to perform hot rolling so that it is 380°C or more and 440°C or less. In the hot rolling process, it is preferable to perform hot rolling so that the temperature of the clad plate at the time of completion is less than 370°C, and it is more preferable to perform hot rolling so that it is 350°C or less. In the hot rolling process, it is preferable to perform hot rolling so that the time from the start to the completion of hot rolling is 60 minutes or less, and it is preferable to perform hot rolling so that it is 40 minutes or less. By performing hot rolling under such conditions, it is possible to more reliably suppress excessive precipitation of Al-Mn-Si compounds and the like in the core material.
[0063] <First cold rolling process> The clad plate after the hot rolling process is completed is subjected to a first cold rolling process without annealing. In the first cold rolling process, one or more passes of cold rolling are performed on the clad plate obtained by the hot rolling process to reduce the thickness of the clad plate so that it is thicker than the desired thickness of the fin material. When multiple passes of cold rolling are performed in the first cold rolling process, annealing is not performed between passes. In the first cold rolling process, for example, cold rolling may be performed so that the reduction ratio, that is, the reduction rate (unit: %) of the thickness of the clad plate by the first cold rolling process relative to the thickness of the clad plate after the hot rolling process is 85.0% or more and 99.5% or less.
[0064] <Annealing process> After the first cold rolling step is completed, the clad sheet is heated and annealed in an annealing step. In the annealing step, the total diffusion amount M calculated by the following formula (1) is 1.0 × 10 -14 m 2 Above 5.0×10 -12 m 2 The clad plate is heated under the following conditions:
[0065]
number
[0066] In the above formula (1), n is the number of intervals when the total heating time is divided by the unit time Δt, and D0 is 1.37 × 10 -5 m 2 / s, Q is 123 kJ / mol, the value of R is 8.3145 kJ / (mol K), and the value of T(k) is the heating temperature [K] at the start of the kth interval.
[0067] When the clad plate is heated in the annealing process, aluminum atoms diffuse and the crystal lattice is rearranged. By controlling the amount of aluminum atoms diffused in the annealing process within an appropriate range, the crystal texture of the core material in the clad plate after the annealing process can be controlled to a desired state, and the crystal texture of the core material in the final fin material can be made to be the specific state.
[0068] More specifically, the self-diffusion coefficient D of aluminum atoms is expressed by the following formula (3) using the temperature T (unit: K) of the clad plate. D = D0exp(-Q / RT) (3)
[0069] Therefore, when the temperature T is constant, the diffusion amount of aluminum atoms can be calculated by multiplying the diffusion coefficient D calculated by the above formula (3) by the holding time. However, in an actual annealing process, the temperature may fluctuate, for example, from the start of heating to the time when the holding temperature is reached, or from the end of heating to the time when cooling is completed. In the above formula (1), the period from the start of annealing to the end of annealing is divided into unit times Δt, and the value of the total diffusion amount M is calculated by summing up the products of the self-diffusion coefficient and the unit time Δt in each section. Therefore, according to the above formula (1), the total diffusion amount M can be calculated taking into account the above-mentioned temperature fluctuations.
[0070] In the manufacturing method, by heating the clad plate in the annealing step so that the total diffusion amount M falls within the specific range, aluminum atoms are appropriately diffused, and the brass orientation, S orientation, and copper orientation are developed in the core material, while the development of the cube orientation, CR orientation, and P orientation in the core material is suppressed. As a result, the crystal texture of the core material in the finally obtained fin material can be made to have the specific aspect.
[0071] The total diffusion amount M during the annealing process is 1.0×10 -14 m 2 If the total diffusion amount M is less than 5.0×10, the development of the brass, S and copper orientations tends to be insufficient. -12 m 2 If the total diffusion amount M in the annealing process is larger than the above range, the development of the Cube orientation, the CR orientation, and the Copper orientation is likely to be promoted. Therefore, if the total diffusion amount M in the annealing process is outside the above specific range, the formability of the fin material may be deteriorated.
[0072] In calculating the total diffusion amount M, the unit time Δt may be set to an appropriate value so that the difference between the temperature of the clad plate at the start of each section and the temperature of the clad plate at the end of each section is sufficiently small. The unit time Δt may be set to, for example, 1 minute.
[0073] <Second cold rolling process> In the second cold rolling step, the clad plate after the annealing step is subjected to one or more passes of cold rolling to obtain a fin material of a desired thickness. When multiple passes of cold rolling are performed in the second cold rolling step, annealing is not performed between passes. EXAMPLES
[0074] Examples of the aluminum alloy fin material and its manufacturing method will be described below. Note that the specific aspects of the aluminum alloy fin material and its manufacturing method according to the present invention are not limited to the aspects of the following examples, and can be appropriately changed within the scope of the present invention.
[0075] As shown in FIG. 1, the fin material 1 of this example is composed of a brazing sheet including a core material 2 and a brazing material 3 arranged on both sides of the core material 2. The core material 2 has chemical components including Si: 0.02% by mass to 0.80% by mass, Fe: 0.02% by mass to 0.80% by mass, and Mn: 0.8% by mass to 2.0% by mass, with the balance being Al and unavoidable impurities. The core material 2 also has a crystal texture in which the orientation density of at least one of the crystal orientations of Brass orientation, Copper orientation, and S orientation is 20 times or more that of a random orientation sample, and the orientation density of the Cube orientation, CR orientation, and P orientation is all 10 times or less that of a random orientation sample. The brazing material 3 is composed of an Al-Si alloy including Si: 6.0% by mass to 13.0% by mass, and Fe: 0.02% by mass to 0.80% by mass. The cladding ratio of each brazing material 3 is 6% or more and 16% or less. The configuration and manufacturing method of the fin material 1 of this example will be described in more detail below.
[0076] The chemical composition of the core material 2 used in this example is shown in Table 1. The chemical composition of the brazing material 3 used in this example is shown in Table 2. The symbol "Bal." in Tables 1 and 2 indicates the balance, and the symbol "-" indicates that the content of the corresponding element is below the detection limit of the spark discharge optical emission spectrometer.
[0077] [Table 1]
[0078] [Table 2]
[0079] In producing the fin material 1 of this example, first, a core material ingot having the chemical composition shown in Table 1 and a brazing material ingot having the chemical composition shown in Table 2 are produced by semi-continuous casting (casting process). For the core material ingots having the chemical compositions shown in alloy symbol A1 and alloy symbols A3 to A6, the core material ingots after casting are held at a temperature of 500°C for 8 hours for homogenization. For the core material ingots having the chemical composition shown in alloy symbol A2, the homogenization process is not performed. The surfaces of the core material ingots and brazing material ingots thus obtained are chamfered to remove the ingot segregation layer. In addition, in this example, the brazing material ingots are hot-rolled, and the thickness of the brazing material ingots is adjusted so that the cladding ratio of the finally obtained fin material is a desired value.
[0080] Next, the brazing material blocks are layered on both sides of the core material block in the combination shown in Table 3 to produce a clad block (lamination process). After preheating the clad block, it is hot rolled to obtain a clad plate (hot rolling process). Next, the clad plate is cold rolled to reduce the thickness of the clad plate until it is thicker than the desired thickness of the fin material (first cold rolling process).
[0081] After the first cold rolling process is completed, the clad plate is heated and annealed (annealing process) under conditions that result in a total diffusion amount M of the value shown in Table 3. The clad plate is then further cold rolled to reduce the thickness of the clad plate to the value shown in Table 3 (second cold rolling process). By the above steps, the fin material 1 (test materials S1 to S3) shown in Table 3 can be obtained.
[0082] In this example, for convenience, the brazing filler metal 3 laminated on one surface of the core material 2 is referred to as the first brazing filler metal 3a, and the brazing filler metal 3 laminated on the other surface is referred to as the second brazing filler metal 3b. The cladding ratios of the first brazing filler metal 3a and the second brazing filler metal 3b are as shown in Table 3.
[0083] Moreover, test materials S4 to S6 shown in Table 3 are test materials for comparison with test materials S1 to S3. The method for producing test materials S4 to S6 is the same as the method for producing test materials S1 to S3, except that the heating conditions in the annealing process were changed so that the total diffusion amount M fell outside the specific range.
[0084] A method for evaluating the crystal texture of the fin material 1, a method for measuring the work hardening exponent, and a method for evaluating the strength of the fin after brazing will be described below.
[0085] <Method of evaluating crystal texture> A square test piece with sides of 25 mm is taken from the center of the fin material 1 in the direction perpendicular to the rolling direction. A surface of this test piece measuring 25 mm long and 25 mm wide is polished until the thickness of the test piece is half that of the fin material, exposing the core material 2. Next, the test piece is immersed for 10 seconds in an etching solution made of a mixture of nitric acid, hydrochloric acid, and hydrofluoric acid, and the surface of the core material 2 is etched.
[0086] Next, the surface of the core material 2 in the test piece is irradiated with X-rays, and X-ray diffraction measurement is performed by the reflection method. This allows a pole figure of the surface of the core material 2 to be obtained. Then, a three-dimensional analysis of the pole figure of the core material 2 is performed by a series expansion method using spherical harmonics, and the orientation density of each crystal orientation present in the core material 2 is calculated. Similar measurements and analyses are performed on a random orientation sample, and the orientation density of each crystal orientation present in the random orientation sample is calculated. Note that as a random orientation sample, a sample in which the crystal orientation is not oriented in a specific direction, such as aluminum powder, may be used.
[0087] Then, the ratio of the orientation density of the core material 2 to the orientation density of the random orientation sample is calculated. The ratio of the orientation density of the crystal orientation in each test material is the value shown in Table 3.
[0088] <Method of measuring work hardening index> A No. 13B test piece as specified in JIS Z2241:2011 is taken from the fin material 1 so that the longitudinal direction is parallel to the rolling direction. Next, a tensile test is performed in a room temperature environment according to the method specified in JIS Z 2241:2011. Then, from the test force-strain curve obtained by the tensile test, the test force and plastic strain values at the yield point and the test force value at the point where the plastic strain has increased by 0.1% from the yield point are identified. Then, using these values, the work hardening index is calculated by the two-point method. The work hardening index of each test material is the value shown in Table 3.
[0089] <Evaluation of fin strength after brazing> The strength of the brazed fin can be evaluated based on the tensile strength of the test material heated under conditions simulating the brazing heating. Specifically, first, the fin material 1 cut to an appropriate size is placed in a brazing furnace and heated in a nitrogen atmosphere. When the temperature in the furnace reaches 600°C, the heating is completed and the fin material 1 is cooled in the furnace. After the fin material 1 is taken out of the brazing furnace and naturally cooled to room temperature, a No. 13B test piece specified in JIS Z2241:2011 is taken from the fin material 1 so that the longitudinal direction is parallel to the rolling direction.
[0090] Using the test pieces thus prepared, tensile tests are performed at room temperature in accordance with the method specified in JIS Z 2241: 2011. Table 3 shows the tensile strength of each test material after brazing.
[0091] [Table 3]
[0092] As shown in Tables 1 to 3, the test materials S1 to S3 each have a core material 2 having the specific chemical composition and crystal texture, and a brazing material 3 having the specific chemical composition. The cladding ratio of the brazing material 3 in the test materials S1 to S3 is all within the specific range. The test materials S1 to S3 having such a configuration each have a high work hardening index, excellent formability, and excellent strength after brazing heat.
[0093] On the other hand, the test materials S4 to S6 were annealed under conditions in which the total diffusion amount M was larger than that of the test materials S1 to S3. Therefore, in the test materials S4 to S6, the aluminum atoms of the core material were excessively diffused during annealing, and the orientation density of the brass orientation, S orientation, and copper orientation was reduced, while the development of the cube orientation, CR orientation, and copper orientation was promoted. As a result, the test materials S4 to S6 had inferior formability compared to the test materials S1 to S3. [Explanation of symbols]
[0094] 1 Fin material 2 Heartwood 3 Brazing material
Claims
1. An aluminum alloy fin material comprising a brazing sheet having a core material and a brazing material disposed on both sides of the core material, The core material is A chemical composition containing Si: 0.02 mass% or more and 0.80 mass% or less, Fe: 0.02 mass% or more and 0.80 mass% or less, and Mn: 0.8 mass% or more and 2.0 mass% or less, with the balance being Al and unavoidable impurities; a crystal texture in which the orientation density of one or more of the Brass orientation, Copper orientation, and S orientation is 20 times or more that of a random orientation sample, and the orientation densities of the Cube orientation, CR orientation, and P orientation are all 10 times or less that of a random orientation sample; The brazing material is made of an Al-Si alloy containing Si: 6.0 mass% or more and 13.0 mass% or less and Fe: 0.02 mass% or more and 0.80 mass% or less, An aluminum alloy fin material, wherein the cladding ratio of each of the brazing filler metals is 6% or more and 16% or less.
2. The aluminum alloy fin material according to claim 1, wherein the core material further contains Zn: 0.3 mass% or more and 3.0 mass% or less.
3. The aluminum alloy fin material according to claim 1 or 2, wherein the Al-Si alloy constituting the brazing material further contains Sr: 0.005 mass% or more and 0.050 mass% or less.
4. A method for producing an aluminum alloy fin material according to any one of claims 1 to 3, a casting process for producing an ingot for a core material having a chemical composition containing Si: 0.02% by mass to 0.80% by mass, Fe: 0.02% by mass to 0.80% by mass, Mn: 0.8% by mass to 2.0% by mass, with the balance being Al and unavoidable impurities, and an ingot for a brazing material made of an Al-Si alloy containing Si: 6.0% by mass to 13.0% by mass and Fe: 0.02% by mass to 0.80% by mass; a lamination step of disposing the brazing material block on both sides of the core material block to prepare a clad block; a hot rolling step of hot rolling the clad ingot to produce a clad plate; a first cold rolling step of cold rolling the clad plate; The clad sheet after the first cold rolling step is subjected to a total diffusion amount M calculated by the following formula (1) of 1.0 × 10 -14 m 2 Above 5.0 x 10 -12 m 2 An annealing process of heating and annealing under the following conditions; A second cold rolling process of cold rolling the clad plate after the annealing process. [0010] (In the above formula (1), n is the number of intervals when the total heating time is divided by the unit time Δt, and D 0 is 1.37 x 10 -5 m 2 / s, Q is 123 kJ / mol, the value of R is 8.3145 kJ / (mol·K), and the value of T(k) is the heating temperature [K] at the start of the kth section.
Citation Information
Patent Citations
Aluminium alloy fin material for brazing and manufacturing method of same
CN103290279A
Aluminum alloy brazing sheet excellent in strength and formability and method for producing the same
JP2012017503A
Aluminum-alloy brazing sheet fin material for heat exchanger, and production process therefor
WO2016147627A1
Aluminum alloy brazing sheet for heat exchangers, and production method for same
WO2017170204A1